The Contribution of Hasan Al-Banna's Thot to Islamic Education: A Case Study of Tarbiyah Halaqohs - Benny Alidasril; Lilia Ulya Amalia; Ellya Roza (Journal of Practice Learning and Educational Development, 2025)
This paper examines the Contribution of Hasan Albanna's thoughts to education, a case study of the Tarbiyah halaqoh. The method uses a literature study (Library research) through books or literature related to the object being studied or supporting documents such as journals and related articles. The results of the study explain that Hasan Albanna has contributed thoughts to Islamic education that he applied to members of the Muslim Brotherhood which are widely adopted by educational institutions today. Hassan al-Banna revived the halaqah system implemented by the Prophet when the early days of da'wah were ordered after ending in the Tabiin period.